Flow Simulations Using Two Dimensional Thermal Lattice Boltzmann Method - Saeed J. Almalowi; Alparslan Oztekin (Journal of Applied Mathematics)
Lattice Boltzmann method is implemented to study hydrodynamically and thermally developing steady laminar flows in a channel. Numerical simulation of two-dimensional convective heat transfer problem is conducted using two-dimensional, nine directional D2Q9 thermal lattice Boltzmann arrangements. The velocity and temperature profiles in the developing region predicted by Lattice Boltzmann method are compared against those obtained by ANSYS-FLUENT. Velocity and temperature profiles as well as the skin friction and the Nusselt numbers agree very well with those predicted by the self-similar solutions of fully developed flows. It is clearly shown here that thermal lattice Boltzmann method is an effective computational fluid dynamics (CFD) tool to study nonisothermal flow problems.